EMPOWERMENT OF HEALTH CADRES IN SUPPORTING THE WELLBEING OF CLIENTS WITH CHRONIC KIDNEY DISEASE (PGK) IN SURABAYA, INDONESIA - minarti, minarti (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Chronic kidney disease (CKD) is a public health problem with an increasing prevalence and incidence of CKD. This increase in incidence is in line with the increase in the incidence of hypertension and diabetes mellitus. Health cadre support for clients with CKD has never been done because specific knowledge about efforts to support health in clients with CKD has never been done. Objective To increase the potential of health cadres through empowerment in order to provide support and motivation for Chronic Kidney Disease clients towards wellbeing. The method used was training including lectures, questions and answers, discussions, role play, pre tests and post tests and the media used: modules and needs identification sheets for CKD clients. Implementation of activities for 3 meetings which are divided into stages of providing material, assigning cadres to identify the support needs of clients, the second meeting discussing the results of identifying needs divided into groups, and the last meeting cadres role play to provide support to clients. The results showed that there was an increase in knowledge before and after empowerment through training. Based on the results of the pre-test assessment, the highest score was 93 and the lowest score was 60, the average score was 70.2, while the highest post-test score was 100 and the lowest score was 67, the average score was 80.4. The difference between post-test and pre-test results ranged from 0-26 points. It was found that more social support needs are needed by CKD clients Empowerment carried out on health cadres is one way to improve wellbeing conditions in CKD clients through various supports. ,